Let’s groove: attachment techniques of Eurasian elk (Alces alces) tooth pendants at the Late Mesolithic cemetery Yuzhniy Oleniy Ostrov (Lake Onega, Russia) - Mannermaa, Kristiina; Rainio, Riitta; Girya, Evgeny Yu.; Gerasimov, Dmitry V. (Archaeological and Anthropological Sciences, 2020)
Abstract More than 4300 Eurasian elk ( Alces alces ) incisors, most of them pendants, were found in 84 burials in the Late Mesolithic cemetery of Yuzhniy Oleniy Ostrov, Northwest Russia. We analysed the manufacture techniques of elk teeth (4014), in the collection of the Peter the Great Museum of Anthropology and Ethnography, St Petersburg. A striking observation is that the manufacture of these pendants is similar in all burials. Teeth were worked by carving one or several grooves around the root tip. In addition to grooved ones, a number of teeth were not worked at all. The uniformity of the chosen species, tooth and techniques indicates that strict norms prevailed in the pendant industry. Despite the overall similarity, our study shows some variation in making pendants. A groove can cut the whole circumference of the root, or several distinct grooves can mark opposite sides of the root. Sometimes the grooves are deep and made carefully, and sometimes they are weak and made hastily. A typology of various groove types was created. In many graves, one groove type dominates. We interpret that this inter-burial variation and domination of one type resulted from personal choice and taste based on practicality. Such variation could also be associated with kin identifiers, but we did not find clear support for that in our study. Our study indicates that the groove types as such had no connection with particular ornaments, garments or hanging positions.